2020
DOI: 10.1080/23311975.2020.1797261
|View full text |Cite
|
Sign up to set email alerts
|

Impact of country-level corporate governance on entrepreneurial conditions

Abstract: The present study examines the effect of country-level corporate governance (CLCG) and Directors' Liability (DL) on Entrepreneurial Framework Conditions (EFCs) across 52 countries from 2014 up to 2017 using balanced panel data and Panel Correction Standard Error estimation. The results revealed that the CLCG has a significant impact across EFCs dimensions. Further, the results declared that the impact of DL is significant and positive in countries that have a high score of DL, but this impact is statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 85 publications
2
12
0
Order By: Relevance
“…Further, it is found that greater board independence is associated with more comprehensive statutory and greater disclosure (e.g., Nelson et al., 2010 ; Chen and Jaggi, 2000 ; Owusu-Ansah and Yeoh, 2005 ; Chen and Jaggi, 2000 ; Juhman 2017 ). Different studies also advocate that there is a positive relationship between board independence and different aspects of financial reporting (e.g., Hashed and Almaqtari, 2020 ; Almaqtari & Hashed et al., 2020 ; Farhan et al., 2020 ; Almaqtari & Shamim et al., 2020 ; Almaqtari & Al-Hattami et al., 2020 ; Al Maqtari et al, 2020 ; Farhan et al., 2020 ). Furthermore, Bradbury et al.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Further, it is found that greater board independence is associated with more comprehensive statutory and greater disclosure (e.g., Nelson et al., 2010 ; Chen and Jaggi, 2000 ; Owusu-Ansah and Yeoh, 2005 ; Chen and Jaggi, 2000 ; Juhman 2017 ). Different studies also advocate that there is a positive relationship between board independence and different aspects of financial reporting (e.g., Hashed and Almaqtari, 2020 ; Almaqtari & Hashed et al., 2020 ; Farhan et al., 2020 ; Almaqtari & Shamim et al., 2020 ; Almaqtari & Al-Hattami et al., 2020 ; Al Maqtari et al, 2020 ; Farhan et al., 2020 ). Furthermore, Bradbury et al.…”
Section: Empirical Analysismentioning
confidence: 99%
“…The study provides an evidence from low-income country. Various studies pointed out that there is a need to examine different issues in emerging and low-income countries (e.g., Al Maqtari et al, 2020Hashed & Almaqtari, 2020). Accordingly the present study provides an insight that similar studies could be conducted in different other emerging and low-income countries contexts.…”
Section: Study Implicationsmentioning
confidence: 57%
“…Moreover, this study examines corporate governance in its moderating role in helping businesses to overcome the challenges posed by the COVID-19 pandemic. This adds a novel point to this study because current literature shows that corporate governance was widely explored in different settings (Kabwe et al , 2021; Rehman and Hashim, 2021, 2020; Aslam and Haron, 2021; Süsi and Jaakson, 2020; Adedeji et al , 2020; Shahar et al , 2020; Al Maqtari et al , 2020; Sadiq et al , 2020; Usman, 2020; Wang et al , 2019), although very few studies have explored it in a moderating role as can be seen in the present research. Furthermore, this study focusses on corporate governance principles (CGP) towards a sustainable and competitive advantage, while most current studies mainly study corporate governance mechanisms and characteristics, such as board components and ownership structure.…”
Section: Introductionmentioning
confidence: 63%